Phenomenon of science in the context of the paradigms of philosophizing - Білецький, І. П. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The article is dedicated to the problem of the outlook foundations of philosophizing. There were pointed out five paradigms: Indian (based on the ideas of reincarnation, samsara and liberation), Chinese (based on the idea of organismism that means the universe is something like a gigantic organism, every person is like an organ of this organism and similar to any organ has its proper place and function or, how the Chinese call it, its proper tao), Antique (based on the idea of looking for happiness in the hostile world), Abrahamic (based on the idea of monotheism and creationism) and Modern scientific (based on the idea of nature science outlook). Peculiarities of the science phenomenon in the Antique, Modern and Abrahamic (partially) paradigms.